Sleep disturbance predicts suicidal ideation during COVID-19 pandemic: A two-wave longitudinal survey. (November 2021) - Wang, Dongfang; Ross, Brendan; Zhou, Xiuzhu; Meng, Dongjing; Zhu, Zhiyi; Zhao, Jingbo; Fan, Fang; Liu, Xianchen
Abstract: Background: This study aimed to examine the cross-sectional and longitudinal associations between sleep disturbance and suicidal ideation (SI) in a large cohort of adolescents experiencing the Coronavirus disease 2019 (COVID-19) crisis in China. Methods: One two-wave longitudinal web-based survey of sleep, SI, and depression was conducted among 67, 905 college students (mean age = 20.23 years, SD = 1.63 years; 31.3% male) during the COVID-19 outbreak (Time1, T1: Feb 3rd to 10th, 2020) and initial remission period (Time2, T2: March 24th to April 3rd, 2020). Results: At T1 and T2, 8.5% and 9.7% of students reported sleep disturbance, 7.6% and 10.0% reported SI, respectively. The prevalence rates of SI at T1 and T2 increased significantly with sleep disturbance and short sleep duration. After adjusting for demographics, pandemic related factors, and depression at T1, sleep disturbance and short sleep duration at T1 were significantly associated with increased risk for SI at T2. Furthermore, sleep disturbance and short sleep duration predicted the new onset and persistence of SI. Conclusion: These findings suggested that sleep disturbance predicts the development and persistence of SI. Early assessment and treatment of sleep disturbance may be an important strategy for prevention and intervention of SI in individuals after exposure to the special public health emergency of COVID-19.